Karakteristik Pembakaran Droplet Campuran Metil Oleat – Etanol dengan Penambahan Multi -Walled Carbon Nanotubes - Yuliati, Lilis; Hamidia, Nurkholis; Ibadurrohman, Ibrahim Ahmad; Pujohastarto, Ilham Ridwan (Jurnal Teknik Mesin Indonesia, 2024)
This research intended to investigate the combustion characteristics of methyl oleic – ethanol blend with OH functionalized multi-walled carbon nanotubes (MWCNT-OH) addition. Methyl oleic is an unsaturated fatty acid methyl ester, which is a constituent of various biodiesels. The observed fuel was a mixture of Methyl oleic with 20% vol of ethanol. MWCNT-OH content was varied by 100 ppm, 200 ppm, 300 ppm, 400 ppm, and 500 ppm (wt based). The presence of ethanol in the droplets is intended to promote the microexplosion phenomenon, generating smaller droplets and a shorter burning time. The experimental results show that the MWCNT-OH addition on the droplet of Methyl oleic – ethanol blend decreased the ignition delay and droplet burning time, while the constant burning rate and droplet temperature (and flame temperature) were increased. Reducing ignition delay time due to the higher thermal conductivity of nanofluid droplets results in more effective heat absorption from the environment and better heat transport inside the droplet. Hence, droplet vaporization, flammable mixture formation and ignition occur in a shorter time. Furthermore, this condition encourages a higher burning rate and a lower droplet burning time. The higher droplet and flame temperatures are related to the higher heating value of the methyl oleic – ethanol – MWCNT-OH mixture and higher droplet burning rate, which results in a higher heat release rate.